2021
DOI: 10.3390/ijerph18052556
|View full text |Cite
|
Sign up to set email alerts
|

Is Youth Smoking Related to the Density and Proximity of Outdoor Tobacco Advertising Near Schools? Evidence from Indonesia

Abstract: Background: Smoking was among the top contributors to deaths and disability as the prevalence among male adults remains high, and that among male youth increases in Indonesia. While local studies have shown high visibility of outdoor tobacco advertising around schools, the country still has no outdoor tobacco advertising ban. Objective: To examine the association between youth smoking behavior and measures of outdoor tobacco advertising density and proximity in Indonesia. Methods: We combined two primary data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
2
8
0
4
Order By: Relevance
“…Also in Surabaya the hotspots were located in areas where many lodgings and rental rooms were available. Evidence from this study show that adolescents are likely targeted by the tobacco industry, as indicated by high density of cigarette retailers [14][15][16] and high density of outdoor tobacco advertisements 13,23 around children and adolescent facilities especially in rural area. The high density of tobacco retailers can give adolescents the perception of wide availability of cigarettes 24 and the easy access to obtain cigarettes which may stimulate tobacco use among adolescents.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also in Surabaya the hotspots were located in areas where many lodgings and rental rooms were available. Evidence from this study show that adolescents are likely targeted by the tobacco industry, as indicated by high density of cigarette retailers [14][15][16] and high density of outdoor tobacco advertisements 13,23 around children and adolescent facilities especially in rural area. The high density of tobacco retailers can give adolescents the perception of wide availability of cigarettes 24 and the easy access to obtain cigarettes which may stimulate tobacco use among adolescents.…”
Section: Discussionmentioning
confidence: 88%
“…High density of outdoor tobacco advertisements around schools is associated with up to 2.16 times increase in the odds of smoking among adolescents. 23…”
Section: Discussionmentioning
confidence: 99%
“…Sedangkan penelitian Prabandari & Dewi (2016), variabel perilaku yang diteliti lebih ke arah persepsi yang dimiliki oleh responden. Secara keseluruhan ketujuh artikel menyatakan adanya hubungan antara iklan dan perilaku merokok (Handayani et al, 2021;Liem, 2014;Prabandari & Dewi, 2016;Purnaningrum et al, 2017;Rachmat et al, 2013;Rizki et al, 2020;Wiryanatha & Ani, 2014). Sebaliknya 2 hasil penelitian terkait domain praktik menunjukkan hasil berbeda yaitu tidak ditemukannya pengaruh antara iklan rokok dengan praktik merokok (Isa et al, 2017;Utami & Susilowati, 2019).…”
Section: P-value Iklan Terhadap Praktik Merokokunclassified
“…Faktor kepadatan iklan rokok di sekitar tempat pendidikan dan tempat tinggal juga berperan besar dalam pembentukan perilaku merokok siswa. Sesuai dengan hasil Handayani, et al (2021), siswa yang lokasi sekolahnya dipadati oleh iklan rokok memiliki kecenderungan 2 kali lebih besar menjadi perokok dibanding mereka yang bersekolah di area yang kepadatan iklannya relatif rendah. Hal ini sejalan dengan penelitian yang dilaksanakan di Kota Padang, meningkatnya iklan rokok berpengaruh pada peningkatan prevalensi perokok usia remaja (Syafrawati et al, 2016).…”
Section: Adanya Pengaruh Iklan Terhadap Praktikunclassified
“…Pemasaran produk rokok melalui iklan rokok sangat memengaruhi perilaku merokok pada remaja pria. Berdasarkan penelitian terbaru terdapat hubungan yang signifikan antara iklan rokok terhadap perilaku merokok pada remaja pria (Handayani et al, 2021).…”
Section: Pembahasanunclassified